Form and Function of Pakpak Traditional House as Cultural Results Material of Cultural Heritage in Pakpak Community - Tampubolon, Flansius; Sinulingga, Jekmen (Budapest International Research and Critics University, 2021)
The purpose of this research to describe the form and function of the Pakpak traditional house in Pakpak Bharat Regency, North Sumatra Province. The form and function of the Pakpak traditional house is described and interpreted from Pakpak language to Indonesian with a semiotic approach to find the meaning and function as well as the cultural value of each ornament that symbolizes the philosophical value of the Pakpak ethnic community through its traditional house. The method used in this study is a qualitative descriptive method with an ethnographic model that is carried out by collecting data carrying out ethnographic activities, namely the main focus of ethnography is to collect data by observation and interviews; work with key informants. The theoretical framework used is a semiotic approach, namely the science that examines signs in human life, the meaning obtained from a sign at the mimetic level cannot be used to express its meaning. This theory is indeed suitable for research that discusses the disclosure of the meaning of the results of material culture in the form of signs on Pakpak traditional houses.